Effects of anode flow channel on performance of air-cooled proton exchange membrane fuel cell. (November 2022) - Yu, Xianxian; Chang, Huawei; Zhao, Junjie; Tu, Zhengkai
Abstract: The cathode channel of an air-cooled proton exchange membrane fuel cell (PEMFC) adopts a straight flow channel for air supply and heat dissipation. Considering the present cathode flow channel, the type of the anode flow channel has an impact on the water and heat management of air-cooled PEMFCs. In this study, we established three-dimensional (3D) multi-physics field models to investigate the performance of three types of anode flow channels: straight flow channel, improved straight flow channel, and serpentine flow channel. Among the three flow channel types under the same voltage condition, the straight flow channel exhibited the best temperature control ability, smallest cathode stoichiometric ratio at the peak power density output, and highest power density. Moreover, the temperature distribution of membrane electrode assembly in the straight flow channel was the most uniform. The coupling of the high cathode air speed and electro-osmotic drag (EOD) easily caused the water loss of anode and cathode membrane electrodes and had an adverse effect on the performance of the fuel cell. The straight flow channel demonstrated the optimal performance with the highest water content. Highlights: Three type of 3D five-layer PEMFC models have been established. Thermal, water and mass transport of air-cooled fuel cell were studied. Straight flow channel is the most appropriate anode type for the air-cooled fuel cell.